1997
DOI: 10.1046/j.1570-7458.1997.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of bibionid larvae in agricultural grassland

Abstract: The distribution of bibionid larvae in agricultural grassland was investigated. They tend to occur sporadically and at low population density. More detailed sampling within a field showed that numbers were highest adjacent to a hedgerow with most being found 6–11 m from the hedge. Log variance/log mean relationships were established for counts of Bibio johannis and Dilophus febrilis larvae collected from soil cores in grassland. Both species were highly aggregated. An area of grassland (160 cm × 80 cm) was div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…This included mainly mobile field-associated taxa, such as thrips and staphylinid beetles, which may have aggregated near hedges through passive dispersal. Other studies have shown the importance of hedgerow proximity for soildwelling species in fields (Alvarez et al, 1997;Blackshaw and DarcyBurt, 1997), which may also be related to shelter effects. In summer, shelter from wind also produces localised warmer and more humid conditions, compared to open fields, which are favoured by many invertebrate species (Forman and Baudry, 1984).…”
Section: Shelter and Microclimatementioning
confidence: 92%
“…This included mainly mobile field-associated taxa, such as thrips and staphylinid beetles, which may have aggregated near hedges through passive dispersal. Other studies have shown the importance of hedgerow proximity for soildwelling species in fields (Alvarez et al, 1997;Blackshaw and DarcyBurt, 1997), which may also be related to shelter effects. In summer, shelter from wind also produces localised warmer and more humid conditions, compared to open fields, which are favoured by many invertebrate species (Forman and Baudry, 1984).…”
Section: Shelter and Microclimatementioning
confidence: 92%
“…Diversas técnicas têm sido utilizadas para determinar variações espaciais de pragas (BLACKSHAW & ARCY- BURT, 1997;FERNANDES et al, 2002;CAMPBELL & MULLEN, 2004;PARK & TOLLEFSON, 2005;PARK & TOLLEFSON, 2006). Dentre essas, a geoestatística (ELLSBURY et al, 1998;FARIAS et al, 2004;BLACKSHAW & VERNON, 2006;FARIAS et al, 2008), que se fundamenta no princípio de que a diferença no valor de uma dada variável, em dois pontos, é dependente da distância entre esses, estando associada às técnicas usadas para analisar e inferir valores de uma variável distribuída no espaço e/ ou no tempo (GARCÍA, 2006).…”
Section: Introductionunclassified
“…Kareiva 1983Kareiva , 1985Marino and Landis 1996;Blackshaw and Arcy-Burt 1997;Svensson et al 2000;Magura 2002), it may be useful to consider the interaction of these factors on the distribution of populations among patches within a landscape. The theory of patch size has concentrated on determining the critical size below which a population will not be able to sustain itself (Slobodkin 1961;Okubo 1984).…”
Section: Introductionmentioning
confidence: 99%